Analisis Pengaruh Pengetahuan Perpajakan, Sanksi Pajak, dan Pendapatan Wajib Pajak Terhadap Kepatuhan Membayar Pajak Bumi dan Bangunan (PBB) Pasca Pandemi Covid-19 di Kecamatan Pakisaji Kabupaten Malang - Habibatut Thoyibah; Nur Diana; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
The purpose of this study was to examine tax knowledge, tax sanctions and taxpayer income on land and building tax payments in Pakisaji District, Malang Regency. This type of research is a correlational quantitative. The population in this study is land and building tax payers in Pakisaji District, Malang Regency. The sample in this study were 120 respondents from Jatisari village who were taken using the slovin formula using purposive sampling technique. The analytical method in this study uses multiple linear regression analysis and uses several types of tests such as instrument tests which consist of validity and reliability tests, normality, classical assumptions consisting of multicollinearity and heteroscedasticity, and hypotheses f, (R2) and partial (t). The test results show that the variables of knowledge of taxation, tax sanctions, and taxpayer income partially have a positive and significant effect on compliance with paying land and building taxes.Keywords: Tax Knowledge, Tax Sanctions, Taxpayer Income, Compliance